Household medication safety practices during the COVID-19 pandemic: a descriptive qualitative study protocol. Issue 11 (24th November 2020) - Grimes, Tamasine C; Garfield, Sara; Kelly, Dervla; Cahill, Joan; Cromie, Sam; Wheeler, Carly; Franklin, Bryony Dean
Abstract : Introduction: Those who are staying at home and reducing contact with other people during the COVID-19 pandemic are likely to be at greater risk of medication-related problems than the general population. This study aims to explore household medication practices by and for this population, identify practices that benefit or jeopardise medication safety and develop best practice guidance about household medication safety practices during a pandemic, grounded in individual experiences. Methods and analysis: This is a descriptive qualitative study using semistructured interviews, by telephone or video call. People who have been advised to 'cocoon'/'shield' and/or are aged 70 years or over and using at least one long-term medication, or their caregivers, will be eligible for inclusion. We will recruit 100 patient/carer participants: 50 from the UK and 50 from Ireland. Recruitment will be supported by our patient and public involvement (PPI) partners, personal networks and social media. Individual participant consent will be sought, and interviews audio/video recorded and/or detailed notes made. A constructivist interpretivist approach to data analysis will involve use of the constant comparative method to organise the data, along with inductive analysis. From this, we will iteratively develop best practice guidance about household medication safety practices during a pandemic from the patient's/carer's perspective. Ethics and dissemination: This study has Trinity College Dublin, University of Limerick and University College London ethics approvals. We plan to disseminate our findings via presentations at relevant patient/public, professional, academic and scientific meetings, and for publication in peer-reviewed journals. We will create a list of helpful strategies that participants have reported and share this with participants, PPI partners and on social media.